The impact of multilateral trading facilities on price discovery: Further evidence from the European markets. Issue 4 (27th August 2019) - Buckle, Mike; Chen, Jing; Guo, Qian; Li, Xiaoxi
Abstract: This study examines relative price discovery for three major European indices, FTSE, CAC, and DAX, their futures and exchange traded funds (ETFs) using the data on 5‐minute intraday transaction prices over a four‐year period. We computed both Hasbrouck (1995) information share with error bounds and Gonzalo and Granger's (1995) common factor weights approach. Gonzalo and Granger's (1995) common factor weights suggest the index futures contracts play a dominant role in price discovery in the CAC market: the CAC 40 index futures lead the price discovery and Lyxor CAC 40 ETFs serving the second resort for information transmission. This could be due to the less frequent trading of ETFs. More importantly, CAC40 under the Gonzalo & Granger (1995) test shows upper and lower error bounds in good range may be the main reason to drive for the meaningful results. In contrast, the upper and lower bounds estimated from the Hasbrouck (1995) are far distant for most cases. Finally, FTSE and DAX markets offer compelling evidence to show that ETFs lead price discovery and spots and futures follows.